Secretion of interleukin-6 by bone marrow mesenchymal stem cells promotes metastasis in hepatocellular carcinoma. Issue 4 (21st July 2017) - Mi, Fei; Gong, Liansheng
Abstract : Mesenchymal stem cells (MSCs) interact with tumor cells and regulate tumorigenesis and metastasis. As one of the important components of the tumor microenvironment, MSC-secreted cytokines play a critical role in cancer development. However, whether and how bone marrow MSCs (BMSCs) and their secreted cytokines participate in hepatocellular carcinoma (HCC) progression, still remains largely unknown. In the present study, we first measured the concentration of interleukin-6 (IL-6) in BMSC conditioned medium (BMSC-CM). Next, we assessed the changes of invasion ability in response to treatment of BMSC-CM or recombinant IL-6 in two human HCC cell lines Bel-7404 and HepG2. Then we analyzed the level of key components of the IL-6 signal pathway, including IL-6 receptor and signal transducer (i.e. IL-6R and gp130), a transcription factor STAT3 (signal transducer and activator of transcription 3), as well as its target genes BCL2, CCND1, MCL1 and MMP2, in BMSC-CM or recombinant IL-6 treated Bel-7404 and HepG2 cells. Results showed that a considerable amount of IL-6 was secreted by BMSCs, and BMSC-CM markedly elevated Bel-7404 cell invasion rate and stimulated the signal transduction of IL-6/STAT3 pathway. Neutralizing the secreted IL-6 bioactivity by the anti-IL-6 antibody diminished the invasion-promoting effect and down-regulated IL-6/STAT3 pathway of BMSC-CM treated Bel-7404 cells. In conclusion, we found that BMSCs may activate the IL-6/STAT3 signaling pathway and promote cell invasion in Bel-7404 cells, suggesting that this protumor effect should be seriously considered before clinical application of MSC-mediated cancer therapy.